Evaluasi Diklat TPS Level GH-LH-SPV PT Bonecom Tricom Dengan Model Kirkpatrick - Wawan Sujatmiko (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
Increasing the competency of human resources in companies is very necessary, companies carry out TPS training, to find out whether the training program is appropriate or not, the companies use the Kirkpatrick method to evaluate the results to find out, reactions, learning, behavior, and results from implementing the TPS training program. Data for evaluation was obtained by distributing questionnaires and interviews to respondents, data was analyzed using descriptive qualitative methods, and data was obtained by distributing questionnaires to 25 respondents and 4 respondents by interviews. The results of the research at the reaction stage, expressed a positive reaction, stating that the implementation of training for participants qualified